PERAN AKTOR LOKAL DALAM FORMULASI KEBIJAKAN EX OFFICIO DI KOTA BATAM - Chi Chi Gita Paramita; R. Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2021)
ABSTRACT The implantation of regional autonomy in Batam City gave birth to dualism or overlapping of authority between the Badan Pengusahaan Batam and Pemerintah Kota Batam which resulted in disharmony in the implementation of government in Batam City. To end this dualism problem, Government Regulation Number 62 of 2019 was formed which explains that the Head of Badan Pengusahaan Batam is led by the Walikota Batam. The purpose of this study was to identify local actors involved in the formulation of ex-officio policies and the role of analyzing each actor. This research is a qualitative research with descriptive method. The result of this study. First, the local actors involved are the Walikota Batam, Badan Pengusahaan Batam, Kadin Batam and Media massa. Second, Walikota Batam and Badan Pengusahaan Batam as the main actors as implementing policies, Kadin Kota Batam and media massa as secondary actors as accelerators. Recommendations in this study are regulated by the Head of BP Batam which should be regulates by an independent party, issuing a PP on the cooperation between BP Batam and Pemerintah Kota Batam and further research.